Efektivitas Pengelolaan Utang Negara oleh Kementerian Keuangan: Analisis Risiko dalam Manajemen Keuangan Makro Saat Ini - Noor Azizah,; Muhammad Zaini,; Muhammad Sainil Abidin,; Totok Adi Prasetyo, (Jurnal Publikasi Ilmu Manajemen, 2025)
This study aims to evaluate the effectiveness of the Ministry of Finance's government debt management within the framework of macrofinancial management in Indonesia. Amid global economic volatility and geopolitical uncertainty, debt management is a crucial instrument for maintaining fiscal sustainability while financing national development. This study uses a qualitative descriptive method with a risk analysis approach that encompasses market risk, liquidity risk, and operational risk. Secondary data were obtained from debt management profile reports and recent macroeconomic indicators. The analysis shows that the Ministry of Finance has successfully maintained the debt-to-GDP ratio within the legally mandated safe limits through a strategy of instrument diversification and optimization of domestic financing sources. However, significant challenges remain from exchange rate fluctuations and the rising trend in global interest rates, which have the potential to increase debt interest burdens. The study concludes that the effectiveness of debt management is currently stable, but that strengthening the early warning system mechanism and closer synergy between monetary and fiscal policies is needed. This study's recommendations emphasize the importance of deepening domestic financial markets to reduce dependence on foreign investors and mitigate the risk of sudden capital outflows.